Co-hydrothermal carbonization of food waste-woody biomass blend towards biofuel pellets production. (November 2018) - Wang, Tengfei; Zhai, Yunbo; Li, Hui; Zhu, Yun; Li, Shanhong; Peng, Chuan; Wang, Bei; Wang, Zhexian; Xi, Yanni; Wang, Siyuan; Li, Caiting
Highlights: Co-hydrothermal carbonization of food waste-woody biomass blend was conducted. High ratio of FW decreased the energy consumption during pelletization. Tensile strength of pellets was increased when WS ratio was increased. High ratio FW during HTC had better combustion behaviors. Abstract: Co-hydrothermal carbonization of food waste-woody biomass blend was conducted to enhance the pelletization and hydrochar-fuel properties. The hydrochar was characterized by proximate, elemental analysis and HHVs, whilst energy consumption of pelletization, tensile strength, and combustion characteristics of hydrochar pellets were evaluated. Results showed that food waste (FW) blended with 0–50% mainly decreased H/C of hydrochar, while blend ratio from 75% to 100% mainly decreased O/C. When FW blended from 0% to 75%, the energy consumption for hydrochar palletization decreased about 12–17 J, whereas tensile strength of pellets increased about 2.4–5.5 MPa by formation of solid bridge when woody biomass (WS) ratio was increased. The hydrochar pellets from high ratio FW had decreased ignition temperature and maximum weight loss rate with wider temperature range, indicating the increased flammability and moderate combustion. These findings demonstrate that HTC of food waste-woody biomass blend was suitable for pelletization towards solid biofuel production.